(untitled) (Symposium on Life and Environmental Sciences, 2026)
Diabetes mellitus is one of the most significant public health problems worldwide and remains a major risk factor for cardiovascular diseases, particularly ischemic heart disease. The prevalence of ischemic heart disease among patients with diabetes mellitus is substantially higher than in the general population, contributing to increased morbidity and mortality rates.